Photodynamic anticancer and antimicrobial activities of novel bacteriochlorins - Tauyakhale, Kaisano Goodness (Rhodes University, Faculty of Science, Department of Chemistry)
The World Health Organization cautioned that the major contributing factors of cancer amongst people are the excessive usage of alcohol, smoking, lack of exercise and low intake of fruits, vegetables, and high-fibre foods. Furthermore, cancer by far is reported to be the most common and leading cause of death worldwide (1 in 6 deaths is due to cancer). Moreover, it is reported that cancer kills more people than tuberculosis, malaria and AIDS combined every year. Chemotherapy has been utilised as a mode of rehabilitation for complete being used in conjunction with surgery or to improve the state of well-being of patients until their point of death. However, it is well known for its adverse effects, such as loss of hair, altered gastric metabolism, vomiting and nausea, dehydration, weight loss, and loss of appetite. For this reason, photodynamic therapy (PDT) was developed as an alternative. A molecular dye (photosensitiser/PS) and light of a specific wavelength produce cytotoxic singlet oxygen species, which induce cell death. The aim of this project is to prepare novel structurally modified porphyrin-type dyes that absorb far into the near-infrared region. Identifying suitable dyes that absorb significantly in the 700âˆ’800 nm region is particularly important from an African perspective, since melanin significantly limits the penetration of laser light into human tissue in the 600âˆ’700 nm region, where first- and second-generation photosensitiser dyes usually absorb. The porphyrin analogues that will be investigated in this regard are bacteriochlorins (BChls), which are known to have suitable optical properties that are potentially suitable in this regard. The first step of the study would be to synthesise tetraarylporphyrins with electron- withdrawing meso-aryl rings because their reduction to BChls is more readily attainable than is the case with electron-donating rings. However, these contrasting properties can be combined to tailor the BChls for effective photodynamic therapy, so the type of porphyrins synthesised will be tetraarylBChls with different meso-aryl groups to first analyze the induction of different chemical properties in this case, the impact of introducing electron donating (4- and 3-quinoline substituents) or electron-withdrawing (pentafluorophenyl substituents) groups on the meso-positions of the dyes and more specifically whether the position of the quinoline nitrogen atom relative to the core of the BChl has any significant impact on the reactivity of the dye (the 4- or 3-position of the quinoline). The next factor to be considered is the induction of the heavy atom effect by introducing a metal in the centre of the dye in order to try to increase the singlet oxygen quantum yields for high production of reactive oxygen species and singlet oxygen and further red shift the lowest energy absorption band of the BChls in the therapeutic window for deep tissue penetration for effective. Lastly, the goal will be to explore whether the delivery of bacteriochlorin photosensitisers to cancer cells can be enhanced by introducing quaternised nitrogen atoms to the meso-aryl ligands.
Keywords: Bacteriochlorin; Porphyrins; Photochemotherapy; Photophysics; Molecules Models; Active oxygen